Individual identification and population assignment with microsatellite markers: an evaluation in two Indian pig populations - BEHL, RAHUL; BEHL, JYOTSNA DHINGRA; NAHARDEKA, N; DAS, G C; KUMAR, K SAJEEV; KUMAR, K ANIL; TANTIA, M S; VIJH, R K (The Indian Journal of Animal Sciences, 2021)
Ability of a set of 24 microsatellite markers for individual identification and their potential for breed assignment of individuals was evaluated in 2 Indian pig populations. The cumulative probabilities of identity of 2 random individuals within a population, even with selected set of 5 loci (CGA, S0026, S0228, S0355, SW936) were 2.87×10–8 (Assamese) and 9.66×10–8 (Anakamali) and from 2 different population was 1.13×10–12. However, the population assignment precision even with all the 24 loci was only 80 (Assamese) and 88% (Ankamali). These results suggested that although this set of markers can be safely employed for identification of individuals but their utility for breed allocation in Indian pigs needs further authentication before they can be practically used for such purposes.